7.
(2b^2+7b^2+b)+(2b^2-4b-12)
(9b^2+b)+(2b^2-4b-12)
9b^2+b+2b^2-4b-12
11b^2+b-4b-12
11b^2-3b-12
8.
(7g^3+4g-1)+(2g^2-6g+2)
7g^3+4g-1+2g^2-6g+2
7g^3-2g-1+2g^2+2
7g^3-2g+1+2g^2
7g^3+2g^2-2g+1
Hope this helps!
Step-by-step explanation:
a−(6a−(5a−8))
a-(6a-5a+8)
a-6a+5a-8
6a-6a-8
0-8
=-8
so the answer doesn't depend on a
Answer:
x+y=-1
Step-by-step explanation:
Answer:
B.) 2(5x-4)(x+1)
Step-by-step explanation:
10x^2+2x-8
= 2(5x^2 + x - 4)
= 2(5x^2 + 5x - 4x - 4)
= 2[5x(x + 1) - 4(x + 1)]
= 2(5x-4)(x+1)